Actuation of shape memory polymer composites triggered by electrical resistive heating. (October 2017) - Murugan, M Sendil; Rao, Sandhya; Chiranjeevi, MC; Revathi, A; Rao, Kavitha V; Srihari, Shylaja; Dayananda, GN
A shape memory polymer is capable of multifunctional performance, be it structural or non-structural. Several actuation mechanisms can be employed to trigger shape memory behaviour. Among these, thermal actuation is most comprehensively studied and applied due to its ease of understanding and utility. However, from the point of view of some niche applications, electrical actuation also needs to be examined. This is all the more relevant for modern aircraft where actuation is amenable to remote computer controls and advanced instrumentation. This in turn paves the way for realizing lightweight and adaptive aircraft structures. In this work, shape memory performance via electrical actuation of unidirectional carbon ply–epoxy shape memory polymer composites has been investigated using an in-house designed test set-up in the manual and automated modes. The synergistic role of carbon plies and the epoxy shape memory polymer matrix for realizing faster shape recovery has been observed. The effect of number of carbon plies on the cyclic shape memory performance of the shape memory polymer composite has also been evaluated. This work demonstrates the feasibility of developing efficient electrically actuated shape memory composites and their potential for different applications.